2006
DOI: 10.1007/s11182-006-0113-x
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter and dark energy of the universe

Abstract: A possibility of existing spheres filled with a uniform constant scalar field in the Universe is shown. These spheres can act as "dark matter" and can be responsible for a decreasing behavior of the "rotational" curved galaxies observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The foregoing production of ordinary matter of the Universe ( ) γ, , ,μ, ,ν... n p e and gravitons can be used as a regular atomic model of the Big Bang [10][11][12][13]. In [14], the possibility of existence of spheres filled with a constant scalar field is proved theoretically, and it is shown that they can act as dark matter and be responsible for a nonexponential behavior of the observed rotational curves of galaxies. Depending on the potential component of the scalar field, these spheres can be found both in the star center and include stars, galaxies, galaxy clusters, and the observed Universe, forming the galactic halo and creating scale hierarchy.…”
Section: Introductionmentioning
confidence: 99%
“…The foregoing production of ordinary matter of the Universe ( ) γ, , ,μ, ,ν... n p e and gravitons can be used as a regular atomic model of the Big Bang [10][11][12][13]. In [14], the possibility of existence of spheres filled with a constant scalar field is proved theoretically, and it is shown that they can act as dark matter and be responsible for a nonexponential behavior of the observed rotational curves of galaxies. Depending on the potential component of the scalar field, these spheres can be found both in the star center and include stars, galaxies, galaxy clusters, and the observed Universe, forming the galactic halo and creating scale hierarchy.…”
Section: Introductionmentioning
confidence: 99%
“…In [3][4][5][6][7], an alternative mechanism for producing massive particles is developed. The solution to the problem of time [3] arising under construction of quantum geometrodynamics, which can be considered as an alternative analog of non-commutation geometry, makes it possible to apply the concept of evolution to the Universe as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, the Universe is an open system [7], whose content and surrounding is a constant uniform scalar field which is a classical vacuum-like medium where the velocity of light is constant in all coordinate systems. The vacuum-like medium which can generate time (a vacuum-like scalar field produces the Lemaître primordial atom) and can be its material carrier (the Lemaître primordial atom can play the role of an atomic clock) can also act as a natural classical instrument realizing selfmeasurement of the Universe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primitive atom can permanently produce ordinary matter by spontaneous emission [4]. Within this approach, the Universe is an open system [5], whose content and surrounding medium are a uniform scalar field. The field is a classical vacuum-like medium where speed of light is constant in all coordinate systems.…”
Section: Introductionmentioning
confidence: 99%